Fatigue in children and adolescents with inflammatory bowel disease: a cross-sectional study - Zuo, Yahui; Cao, Jinjin; Wang, Yuanyuan; Cai, Wenqian; Li, Mei (Frontiers in Pediatrics, 2024)
BackgroundIn recent years, there has been an observed increase in the global diagnosis rate of inflammatory bowel disease among children and adolescents. In inactive disease states, fatigue has emerged as the most debilitating symptom, while in active disease states, it ranks second. However, there remains a notable lack of understanding regarding fatigue in pediatric inflammatory bowel disease patients. Consequently, this study sought to investigate the prevalence and status of fatigue in a cohort of pediatric inflammatory bowel disease patients in China.MethodsA cross-sectional, questionnaire-based survey was conducted. The researchers recruited 110 patients with inflammatory bowel disease using the convenient sampling method between 1 September 2021 until 31 November 2022 in Department of Gastroenterology of Children's Hospital of Nanjing Medical University. Fatigue was assessed using the Multidimensional Fatigue Scale, while potential factors associated with fatigue were analyzed through univariate and multiple regression analyses.ResultsThe study found that the total score of fatigue in children with inflammatory bowel disease was 62.22 ± 20.55. The univariate analysis revealed significant differences in the degree of fatigue across regions, ages, disease severities, corticosteroid use, and biological agent use. Furthermore, the multiple regression analysis indicated a significant difference in BMI (p < 0.05).ConclusionsFatigue is a multidimensional symptom that affects a majority of pediatric inflammatory bowel disease patients. Factors such as patient region, age, disease severity, BMI, and drug use are significantly associated with fatigue. Healthcare providers should prioritize the assessment of fatigue symptoms in these patients. Following the initial assessment, targeted interventions should be implemented to alleviate and improve these symptoms.